2022
DOI: 10.3389/fimmu.2022.999849
|View full text |Cite
|
Sign up to set email alerts
|

A novel cuproptosis-related subtypes and gene signature associates with immunophenotype and predicts prognosis accurately in neuroblastoma

Abstract: BackgroundNeuroblastoma (NB) is the most frequent solid tumor in pediatrics, which accounts for roughly 15% of cancer-related mortality in children. NB exhibited genetic, morphologic, and clinical heterogeneity, which limited the efficacy of available therapeutic approaches. Recently, a new term ‘cuproptosis’ has been used to denote a unique biological process triggered by the action of copper. In this instance, selectively inducing copper death is likely to successfully overcome the limitations of conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…NB is the most common extracranial tumor in children, and there is currently no standardized prognostic evaluation system, which due to NB is a highly heterogeneous tumor ( 5 , 10 ). Despite the utilization of genetic testing techniques in clinical practice, only a limited number of genes have established prognostic value in NB ( 24 , 25 ). It is still unclear why some patients experience poor clinical outcomes despite the absence of commonly detected high-risk genes, while others exhibit positive clinical outcomes despite the presence of individual high-risk gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NB is the most common extracranial tumor in children, and there is currently no standardized prognostic evaluation system, which due to NB is a highly heterogeneous tumor ( 5 , 10 ). Despite the utilization of genetic testing techniques in clinical practice, only a limited number of genes have established prognostic value in NB ( 24 , 25 ). It is still unclear why some patients experience poor clinical outcomes despite the absence of commonly detected high-risk genes, while others exhibit positive clinical outcomes despite the presence of individual high-risk gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.1; **p < 0.05; ***p < 0.01; ****p < 0.001, respectively. limited number of genes have established prognostic value in NB (24,25). It is still unclear why some patients experience poor clinical outcomes despite the absence of commonly detected high-risk genes, while others exhibit positive clinical outcomes despite the presence of individual high-risk gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…A second study by Olou et al pointed to its involvement in adipocyte maintenance and secretion of the cancer-promoting cytokine IL-6 [27]. Finally, Tian et al showed that silencing this gene suppressed proliferation, migration, and invasion in neuroblastoma [28]. Within mitochondrial proteins exhibiting a decrease, the two enzymes of the TCA cycle, succinate dehydrogenase (encoded by Sdha) and fumarate hydratase (encoded by Fh), which represent potential tumor suppressors, were frequently reported to be downregulated in cancers [29,30].…”
Section: Discussionmentioning
confidence: 99%